Bacterial Community Composition and Presence of Plasmids in the Endosphere- and Rhizosphere-Associated Microbiota of Sea Fig (Carpobrotus aequilaterus) - Angela M. Sánchez-Salazar; Jacquelinne J. Acuña; Michael J. Sadowsky; Milko A. Jorquera (Diversity, 2023)
The plant microbiome is one of the most important environments for ecological interactions between bacteria that impact the plant and the ecosystem. However, studies on the diversity of mobile genetic elements (such as plasmids) associated with the plant microbiome are very scarce. Here, we determined the bacterial community composition and the occurrence of plasmids in the microbiota associated with sea fig, Carpobrotus aequilaterus (N.E. Br.), a succulent species widely used as an ornamental plant in Chile. The abundance and composition of the endophytic and rhizospheric bacterial communities were determined by quantitative PCR (qPCR) and DNA metabarcoding analysis. Plasmid diversity in the plant microbiome was determined by plasmid DNA extraction and screened by endpoint PCR of backbone genes for four different incompatibility groups (Inc). The results showed about 106 copies of the 16S rRNA gene in the endosphere and rhizosphere, showing significant differences according to the diversity index. Proteobacteria (Pseudomonadota; 43.4%), Actinobacteria (Actinomycetota; 25.7%), and Bacteroidetes (Bacteroidota; 17.4%) were the most dominant taxa in both plant compartments, and chemoheterotrophy (30%) was the main predicted function assigned to the microbiota. Plasmid diversity analysis showed the presence of transferable plasmids in the endosphere and rhizosphere of C. aequilaterus, particularly among environmental plasmids belonging to the IncP and IncN incompatibility groups.